Practical and modal possibilities based on real acts in the course Introduction to the Philosophy of Edmund Husserl - Sánchez Soberano, Ramsés Leonardo (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
What can it mean for the phenomenological analysis that modalization consists in a primitive intentional variation according to a horizonts formally founded? What would be a variation of this order and how it is related to the philosopher’s life and his temporality? To these questions we need to ad done more. How to discover the formal correspondences that do not vary and what holds all contents in any act of conscience? The variations described in the following pages should be considered as acts that emerge from possibilities, acts of presumption, doubtfulness, probability, etc., but also as statements in which we say something is wrong or invalid, namely, those the type «this is really so». If we take the latter, this means that synthetic events are given in «modes» complexes that should be supported in simple certitudes because, by nature, modalities should be based on «the simple pure certitude» understood as his «primitive mode».